An analysis of thermo-magnetic convection of paramagnetic fluid in rectangular enclosure - Anna Kraszewska; Łukasz Pyrda (ACTA INNOVATIONS, 2016)
The thermo-magnetic convection of paramagnetic fluid in a strong magnetic field is studied. The fluid is aqueous solution of glycerol with gadolinium nitrate hexahydrate. Experimental enclosure – rectangular vessel with aspect ratio equal to 2 – was heated from the bottom, and cooled from the top. Temperature difference between top and bottom walls was kept constant ΔT=5K. The magnetic induction was increased stepwise from 1 to 10 [T]. On the basis of temperature measurements, analysis of heat transfer and fluid flow were performed, showing that magnetic field strongly enhance heat transfer (over 300%) and that aspect ratio of the enclosure has a great influence on heat exchange in the system.